The Effects of an Inadequate Data Bank System on Real Estate Agency Practice in Lagos Mainland, Nigeria - Ademola Farinmade; Toluwaniyin Inioluwa Akinyemi (URBAN AND REGIONAL PLANNING REVIEW, 2023)
Property data is an essential component and an integral part of decision-making accountability, so making bad decisions is inevitable in its absence. Therefore, the lack of crucial data being a major factor impacting real estate agency firms and forms the crux of this study. This study examines the impact of a deficient data bank system's impact on licensed estate agents' practice. The study was conducted using questionnaires administered to Estate Surveyors and Valuers within Lagos Mainland. A sample size of 192 respondents was selected from the Nigerian Institution of Estate Surveyors and Valuers' Directory, which was used for the analysis. The study revealed that the unavailability of a central property data system impairs, to a great extent, the practice of real estate agents. The study further revealed that there is a need for members of the Nigerian Institution of Estate Surveyors and Valuers to collaborate and create a robust databank comparable to that of the Investment Property Databank (IPD). It was then suggested that measures be put in place to develop and facilitate the running of a databank. This would then be made available and accessible to Estate Surveyors that require such information.